Intervenciones del profesional de enfermería en el acompañamiento prenatal a gestantes con diagnóstico positivo de VIH/SIDA (2021)
The Human Immunodeficiency Virus (HIV) and in its final stage the Syndrome of Acquired Immunodeficiency (AIDS), continue to occur in alarming numbers throughout the world. world, with developing countries being the most affected by this infection. Mother-to-child transmission of HIV is a problem that has become visible in recent years, when we talk about mother-to-child transmission of HIV, reference is made to the contagion of a seropositive pregnant woman to her child during the development of pregnancy, childbirth or lactation, which generates infection to the newborn by contact with fluids from the mother. Worldwide, around 1.4 million women living with HIV are in gestation and the probability of transmitting the virus to their children, varies between rates of 15 to 45%, however, if preventive measures are implemented with the implementation of the protocol of maternal and child prevention this rate is reduced to 5%, therefore, it is essential to have with adherence to retrovirals and medical follow-up, since the risk is slightly reduced more than 1% if antiretrovirals are given to pregnant women and newborns in crucial moments with risk of developing infection.(1) The nursing professional is the one who carries out the educational activities in the control prenatal, in addition to monitoring the pregnancy in terms of the management of paraclinical and consultations with other disciplines, therefore, it is the one that closely accompanies the pregnant woman living with HIV, that is why it is necessary for these professionals to have with information proper to nursing care that a patient in this condition needs.